Dilema Perceraian Suami Muslim Pegawai Negeri Sipil di Propinsi Bengkulu - Toha Andiko; Fauzan Fauzan (Al-Ulum, 2019)
This article examines the problem of Muslim husband civil servants (ASN) who are going to divorce, obtaining permission from officials in their place of work, must go through a long and quite long hierarchical procedure. The stages passed by husbands who work under the City and Regency Governments are longer and longer, compared to those working in the Ministry of Religion. The husband who submits divorce application without written permission from the official, then he is threatened with severe disciplinary punishment. In addition, if the husband submits a divorce application for no reason according to PP No. 45 of 1990, will be deducted 2/3 of his salary, and if there are no children, then his salary is 1/2 for his ex-wife. As a result, the ex-husband became difficult to remarry because his salary was severely deducted. As a result, the majority of husbands chose to remain in their marital status, even though they had separated the house. However, there are also several husbands who manipulate their wife’s condition so that they are not subject to the rules.